Orientation-specific adaptation to mentally generated lines in human visual cortex - Mohr, Harald M.; Linder, Nicolas S.; Linden, David E.J.; Kaiser, Jochen; Sireteanu, Ruxandra (NeuroImage (Orlando, Fla.), 2009)
Previous studies have shown that prolonged inspection of a tilted visual pattern leads to changes in perception (“tilt after-effect”, TAE), as well as to a reduction of the neural activation evoked by this pattern (“neural adaptation”). In this fMRI study, we investigated whether such perceptual and neural adaptation can be induced solely by mental imagination. The subjects were asked to mentally generate tilted lines, after which they were presented test lines oriented in the same or the direction orthogonal to the mentally tilted lines. Subjects showed a TAE even after mental imagery (“mental TAE”). Furthermore, a significant orientation-specific adaptation occurred in extrastriate visual areas (V3–V4), showing a decreasing gradient of adaptation from areas V4 to V1. Both this neural adaptation and the individual size of the mental TAE correlated with performance in a behavioural task probing mental imagery. Thus, orientation-selective neurons in visual areas seem to be recruited by mental imagery, and the amount of recruitment correlates with the degree of success of mental imagery operations. The influence of mental imagery on perception and on the neural activity in extrastriate visual areas provides evidence for analogue coding of mental images.